Control of the tropical mite Polyphagotarsonemus latus (Banks, 1904) on cotton with chemical pesticides, two of them applied with "electrodyn" - Mariconi, F.A.M.; Geraldi, F. I.; Biondo, C.J.; Donatoni, J.L.; Clari, A. I.; Raizer, A.J.; Arashiro, F.Y. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
A field test was carried out in Santa Bárbara D' Oeste, State of São Paulo, Brazil, to evaluate the control of the "tropical mite", a major pest on cotton in that area. The treatments were seven with four repetitions (each repetition had 130 m² and each treatment, 520m²). The treatments and active ingredients per hectare were as follows: A) check; B) dicofol, 555g; C) bromopropylate, 129g; D). abamectin plus multimethyl alquenol, 6g + 11,44g; E) Dicofol,364g; F) profenophos, 500g; G) abamectin, 12g. Treatments C and E were special solutions applied with "Electrodyn". Five counts of the mite were made: the first, one day before the spray and 04, 07, 13 and 17 days after spraying. The best results were obtained with treatments E and D (07 days), B, D and E (13 days) and E (17 days), (tables II and III). Counts of predator mites were made also (table IV).